Nepalese EFL Teachers’ Digital Literacy for Online Teaching - Saud, Mohan Singh (REiLA : Journal of Research and Innovation in Language, 2021)
The face-to-face mode of delivery had significantly been affected by the COVID-19 pandemic. Due to its spread, the government had suspended the traditional classroom teaching system, requiring its alternative online teaching instead. Accordingly, English teachers needed to be prepared with the necessary digital literacy skills for effective online teaching. Considering this situation, this study sought to survey the digital literacy skills of secondary school level English teachers of Nepal to check their preparedness for online delivery. A questionnaire was prepared through Google Docs and circulated to English teachers through emails and Messenger. Data was collected using the snowball-sampling method. Altogether, 426 English teachers across the country participated in this study. This study found that secondary school-level English teachers possess the necessary digital literacy skills like word processing, the use of the Internet, downloading, online presentations, and hence, are prepared for an online teaching mode.